Vitamin D Deficiency: A Global Health Problem - Geir Bjørklund (Annals of Environmental Science and Toxicology - Peertechz Publications, 2016)
Vitamin D deficiency is a global health problem. The extent of vitamin D deficiency varies with latitude, season and sun exposure. Also the degree to which the body of religious or cultural reasons is covered, the skin color and, not least, dietary habits and the use of supplements has an impact on the vitamin D status. Women are more prone to develop vitamin D deficiency than men.